Main Factors Affecting the Environment and their Consequences - Alisherovna, Kazakova Amina; Khasanovna, Mansurova Malika (American Journal of Bioscience and Clinical Integrity, 2025)
The severity of ecological situations is determined by many factors: the specialization and combination of developing industries, the scale of production and related technogenic emissions, the methods of economic management, the population density of the area, and the natural capacity of the local ecosystem to endure human pressure. This article provides an overview of the main ecological problems and their direct influence on the human body. It was found that young people are the most vulnerable to negative environmental impacts. The article also presents a list of common environmental diseases.